2011
DOI: 10.1002/ajmg.a.34192
|View full text |Cite
|
Sign up to set email alerts
|

Axial spondylometaphyseal dysplasia: Additional reports

Abstract: Axial spondylometaphyseal dysplasia (SMD) (OMIM 602271) is an uncommon skeletal dysplasia characterized by metaphyseal changes of truncal-juxtatruncal bones, including the proximal femora, and retinal abnormalities. The disorder has not attracted much attention since initially reported; however, it has been included in the nosology of genetic skeletal disorders [Warman et al. (2011); Am J Med Genet Part A 155A:943-968] in part because of a recent publication of two additional cases [Isidor et al. (2010); Am J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Patients with SDS can exhibit mild vertebral abnormality (usually square vertebral bodies; Nishimura et al 2007). This was noted in our case and in at least one of the patients described by Suzuki et al (2011); this patient received initially a tentative diagnosis of SDS. However, clinically, patients with SDS should have evidence of pancreatic insufficiency or hematological abnormalities (cytopenia of at least one lineage) that are required for establishment of the clinical diagnosis.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Patients with SDS can exhibit mild vertebral abnormality (usually square vertebral bodies; Nishimura et al 2007). This was noted in our case and in at least one of the patients described by Suzuki et al (2011); this patient received initially a tentative diagnosis of SDS. However, clinically, patients with SDS should have evidence of pancreatic insufficiency or hematological abnormalities (cytopenia of at least one lineage) that are required for establishment of the clinical diagnosis.…”
Section: Discussionsupporting
confidence: 74%
“…Notably, although the patient reported here was closely followed for color blindness, nystagmus, and amblyopia since the age of 2 years, clinically apparent retinal changes were identified only at 16 years of age, leading to the clinical diagnosis. In previous reports, retinitis pigmentosa was diagnosed as early as in the neonatal period (age 3 weeks; Suzuki et al 2011) and up to 9 years of age; a few of the reported patients ultimately became blind (Krakow et al 2009; Isidor et al 2010). …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The symptoms of SMD vary depending on the age of the patients (1) , the principal symptoms being as follows: limited postnatal growth; rhizomelic shortening of the limbs in early childhood evolving to shortening of the trunk by the age of 10 years; thoracic hypoplasia, which causes respiratory problems in the neonatal period and increases susceptibility to respiratory tract infection (4) ; scoliosis with dorsal kyphosis; abnormalities of the metaphyses and pelvis (5) ; odontoid hypoplasia; and valgus of the knees and claudication (6) , the latter typically being the first sign of the disease (2) . There might be little or no ossification of the cervical vertebrae, leading to cervical instability and swan neck deformity (7) .…”
mentioning
confidence: 99%